Pola Peresepan Obat Diare pada Pasien Balita di Instalasi Rawat Jalan RSUD Kajen Kabupaten Pekalongan Periode Januari – Juni 2024 - Adinda Oktavianasari; Rismi Fatoni (STIKes Ibnu Sina Ajibarang, 2025)
Diarrhea generally attacks toddlers under 5 years of age because toddlers' immune systems are still in the weak category, so they are more susceptible to exposure to bacteria that cause diarrhea. The Central Java Provincial Health Service recorded 179,172 or 46.3% of the highest cases of diarrhea found in health facilities. The aim of this research was to determine the prescribing patterns used for toddler patients in the outpatient installation of Kajen Regional Hospital, Pekalongan Regency. This type of research is non-experimental using a descriptive design with a quantitative approach and collecting data retrospectively using medical record data. The inclusion criteria in this study were diarrhea patients aged 0-5 years in the outpatient installation of Kajen Regional Hospital during January – June 2024 who received treatment for diarrhea without a diagnosis of chronic disease using purposive sampling data collection techniques. The research was conducted on 66 patients who met the inclusion criteria with the results of the characteristics of the patients who suffered the most from diarrhea being 56.06% male, 63.64% aged 0-1 year. The most frequently prescribed class of drugs is zinc at 47.06% and the least prescribed class of drugs is oral rehydration at 0.84%.